1984
DOI: 10.1210/jcem-58-3-410
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Extrapituitary Mechanisms Mediating the Morning Peak of Plasma Cortisol in Man*

Abstract: There is evidence for the existence of ACTH unrelated mechanisms in the regulation of cortisol secretion in man. This study was designed to elucidate the interrelationship between plasma ACTH and cortisol levels during the increase in cortisol levels, which occurs during morning hours. The results were compared with those of an artificial cortisol peak induced by administration of small amounts of ACTH, and with ACTH and cortisol values during insulin-induced hypoglycemia. In these control groups, the increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Results from experiments in animals and humans give some support that influences of glucocorticoids on the central nervous activity are not limited to negative feed-back regulation of the pituitary-adrenal axis, but pertain to major psychophysiological functions of the brain, as perception and sleep [Henkin, 1975;Beckwith et al, 1983;Weitzman et al, 1983;Fehm et al, 1984;Rees and Gray, 1984], In earlier studies Bom et al, 1986], we have demonstrated that the early morning rise in plasma cortisol is associated with a period of more shallow sleep, which was also in line with findings by Alford etal. [1973], Elevated nocturnal levels of adrenal cortical steroids may be also responsible for sleep disturbances typically observed in patients with endogenous depression [Jarret et al, 1985;Sachar et al, 1970].…”
supporting
confidence: 89%
“…Results from experiments in animals and humans give some support that influences of glucocorticoids on the central nervous activity are not limited to negative feed-back regulation of the pituitary-adrenal axis, but pertain to major psychophysiological functions of the brain, as perception and sleep [Henkin, 1975;Beckwith et al, 1983;Weitzman et al, 1983;Fehm et al, 1984;Rees and Gray, 1984], In earlier studies Bom et al, 1986], we have demonstrated that the early morning rise in plasma cortisol is associated with a period of more shallow sleep, which was also in line with findings by Alford etal. [1973], Elevated nocturnal levels of adrenal cortical steroids may be also responsible for sleep disturbances typically observed in patients with endogenous depression [Jarret et al, 1985;Sachar et al, 1970].…”
supporting
confidence: 89%
“…Third, diurnal variations in adrenal steroidogenesis do not seem to be directly related to plasma ACTH concentrations (31,32), whereas in rats a strict reciprocal diurnal relationship exists between leptin and corticosterone levels (9). It will be interesting to see if leptin is responsible for this discrepancy, which possibly involves other identified pituitary or extrapituitary mechanisms that can influence adrenal steroidogenesis (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…This parallel stimulation of catecholamine and corticosteroid secretion could be a mechanism for the adapta tion to acute stress, since the corticosteroids that pass the adre nal medulla with the centripetal bloodflow stimulate the en zymes of the catecholamine synthesis [31 ]. On the other hand, this mechanism could perhaps be an explanation for the dis crepancy between diurnal ACTH and cortisol plasma levels [32][33][34] since it has been shown that splanchnic nerve innerva tion is important for the diurnal variations in adrenal steroido genesis [35].…”
Section: Discussionmentioning
confidence: 99%